Legal mechanisms to combat terrorism in contemporary international law - منديل, ناظر احمد; شعبان, ياسر عواد (Journal of Legal Sciences, 2019)
The terrorist threat has increased dramatically over the past three decades. After terrorist attacks were carried out in traditional ways and left limited victims and casualties in targeted groups and installations, they were carried out in very precise and sophisticated ways, benefiting from modern technology and losing huge losses, Or property and installations ...Until recently, terrorist operations were usually aimed at hijacking civilian aircraft, abducting individuals, taking and holding hostages (prominent figures, diplomats and even private individuals), as well as dropping bombs and planting unexploded ordnance, but their dangers now escalated depending on the development of the means used and the target groups and facilities. Terrorist groups have taken advantage of everything that would enable them to carry out their operations even at the expense of innocent people.Recently, there have been new manifestations of these terrorist operations, which have been steadily increasing and are linked to the destruction of information through international communication networks. Groups and individuals have become politically motivated and even personal, and even adolescents, motivated by their rush and curiosity, inside their rooms and offices and in front of their computers, For the major companies and national and international institutions far from them, after the world became a small village by the development of means of communication and the flow of news through the road of information. Resulting in significant financial and service losses in a short period of time, and panic and fear among the owners of these programs and institutions.The dangers of the use of chemical and biological weapons by terrorist groups and new means have become increasingly urgent in the international arena, especially after the collapse of the Soviet Union, where more than one question was raised about the fate of its nuclear arsenals. Weapons from the black market in the light of the economic and social problems that accompanied the transformations in Russia after this collapse and the associated difficult situations of a large group of scientists in this regard, in such a way that may make them not withstand the financial temptations of these groups Enable them to provide important information in this regard.In this research, we aim to achieve the main objective of defining the legal mechanisms to combat terrorism by dividing it into two areas according to the following plan:First topic: National and international legal mechanisms to combat terrorismThe second topic: Effectiveness of legal mechanisms and their impact on combating terrorism